Zastosowanie MSSF 1 po raz pierwszy - jego znaczenie i skutki dla budowy sprawozdań finansowych - Gilarski, Zygmunt (IFRS 1: First-Time Adaptation of International Financial Reporting Standards, 2005)
The International Accounting Standards Board published its first International Financial Reporting Standards IFRS l, First-time Adoption of International Financial Reporting Standards, in June 2003. IFRS l replaces SIC-8. The key principle of IFRS is full retrospective application of all IFRS in force at the closing balance sheet date for the first IFRS financial statements. IFRS l is applied by any company that prepares its first IFRS financial statements for a period beginning on or after l January 2004.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 60-66